2019
DOI: 10.3892/ol.2019.10612
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor 1 mutations in 260 cervical cancer samples from Chinese patients

Abstract: Cervical cancer is one of the leading causes of cancer-associated mortality among females; however, the underlying molecular mechanisms of its carcinogenesis remain largely unclear. Previous comprehensive genomic studies have revealed prevalent estrogen receptor 1 (ESR1) mutations in breast cancer, which are rare in certain other types of cancer. To the best of our knowledge, it is unknown whether ESR1 mutations also exist in cervical cancer. Considering the evidence that cervical cancer shares certain genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Estrogen and its analogs can activate estrogen-responsive genes by binding to estrogen receptor α (ERα) ( 7 ). Previous genomic studies have identified frequent mutations of the ERα gene (ESR1) in CC ( 8 , 9 ). Additionally, it has been demonstrated that viral-codified E6 and E7 proteins could directly interact with androgen receptor (AR) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen and its analogs can activate estrogen-responsive genes by binding to estrogen receptor α (ERα) ( 7 ). Previous genomic studies have identified frequent mutations of the ERα gene (ESR1) in CC ( 8 , 9 ). Additionally, it has been demonstrated that viral-codified E6 and E7 proteins could directly interact with androgen receptor (AR) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 According to the reports, there were approximately 75% of BC patients with ER highly expressed. 5 Besides, ER was also found overexpressed in many different kinds of tumors, such as estrogen-dependent ovarian cancer, 6 endometrial cancer, 7 cervical cancer, 8 estrogen-independent liver cancer, 9 gastric cancer, 10 lung cancer, 11 colorectal cancer, 12 etc. ER is therefore considered to be a key indicator in clinical treatment and prognosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To date, the detection of ESR1 mutations has been reported in cervical squamous cell carcinoma [ 26 ] and in a patient with endometrial cancer treated with an aromatase inhibitor [ 27 ]. It has also been reported that the presence of ESR1 mutations is associated with worse outcomes in endometrial cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 mutations have emerged as a key mechanism of resistance to endocrine therapy in patients with ER-positive metastatic breast cancer [ 24 ] and their detection is now considered to be highly promising as a prognostic and predictive biomarker in this type of cancer [ 24 , 25 ]. To date, only a few studies have investigated the presence of ESR1 mutations in endometrial and cervical cancer [ 26 , 27 , 28 , 29 , 30 ]. According to the cBioPortal cancer genomics database, ESR1 mutations have been detected in 4–6% of uterine corpus endometrial carcinoma samples [ 31 ].…”
Section: Introductionmentioning
confidence: 99%